An Enantioselective Synthesis of (5S,6R,11S,14R)-Acremodiol - Dey, Papiya; Chatterjee, Sucheta; Gamre, Sunita S.; Chattopadhyay, Subrata; Sharma, Anubha (Synthesis, 2017)
An expeditious synthesis of the (5S,6R,11S,14R)-isomer of acremodiol was developed via a convergent route. One of the required building blocks was synthesized earlier via two sequential lipase-catalyzed secondary carbinol acetylations. The other unit was derived from (R)-2,3-cyclohexylideneglyceraldehyde as a chiral template. The bismacrolide skeleton was constructed by an intermolecular esterification reaction under Mitsunobu conditions followed by a ring-closing metathesis of the resultant α,ω-dialkenoic ester.
Keywords: asymmetric synthesis; (R)-2,3-cyclohexylideneglyceraldehyde; macrodiolide; ring-closing metathesis; lipase-catalyzed transesterification